Still Platonic After All These Years: Artificial Life and Form/Matter Dualism. - Jonson, Annemarie (Australian Feminist Studies)
This article analyzes concepts on artificial life and theory of vitality proposed by Christopher Langton. Basis of vitality theory on the works of logicians, Turin and Godel; Claims of ALife on the `Central Dogma' of molecular biology; Binary logic on notions of life; Comparison of the distribution of life with a parallel processing computer.